2015
DOI: 10.18632/oncotarget.3344
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of HDAC2 promotes NF-κB-dependent gene expression

Abstract: The transcription factor nuclear factor-κB (NF-κB) is crucial for the maintenance of homeostasis. It is incompletely understood how nuclear NF-κB and the crosstalk of NF-κB with other transcription factors are controlled. Here, we demonstrate that the epigenetic regulator histone deacetylase 2 (HDAC2) activates NF-κB in transformed and primary cells. This function depends on both, the catalytic activity and an intact HDAC2 sumoylation motif. Several mechanisms account for the induction of NF-κB through HDAC2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…27 Individual pharmacologic targeting of Hdac1 vs. Hdac2 is considered very difficult given the nearly identical nature of the their active sites and surrounding surfaces, but there are reports of small molecules that show different dissociation rates for Hdac1 vs. Hdac2; such kinetically-selective Hdac2 inhibitors enhance Treg function in vitro but have not been tested in vivo . 28, 29 An alternate approach is to target the functions of the HDAC-associated complex, though the core components and their partnering molecules may vary by cell type and function. 30 An example of this approach, in the case of the CoREST complex, was the development of dual inhibitors of the HDAC and demethylase activities of the complex, 31 and these inhibitors are under investigation for their effects on Tregs.…”
Section: Hdac Enzymes and Treg Cellsmentioning
confidence: 99%
“…27 Individual pharmacologic targeting of Hdac1 vs. Hdac2 is considered very difficult given the nearly identical nature of the their active sites and surrounding surfaces, but there are reports of small molecules that show different dissociation rates for Hdac1 vs. Hdac2; such kinetically-selective Hdac2 inhibitors enhance Treg function in vitro but have not been tested in vivo . 28, 29 An alternate approach is to target the functions of the HDAC-associated complex, though the core components and their partnering molecules may vary by cell type and function. 30 An example of this approach, in the case of the CoREST complex, was the development of dual inhibitors of the HDAC and demethylase activities of the complex, 31 and these inhibitors are under investigation for their effects on Tregs.…”
Section: Hdac Enzymes and Treg Cellsmentioning
confidence: 99%
“…For example, Wagner et al . described that higher expression level of HDAC2 is closely linked to cisplatin resistance of colon cancer cells. Fritsche et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our present results, mounting evidence indicates that HDAC2 is aberrantly overexpressed in a variety of cancer tissues and implicated in the promotion of malignant phenotypes of certain cancer cells such as anti-cancer drug resistance. For example, Wagner et al [17] described that higher expression level of HDAC2 is closely linked to cisplatin resistance of colon cancer cells. Fritsche et al [18] revealed that HDAC2 contributes to the resistance to etoposide of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this mechanistic uncertainty, our studies have uncovered a remarkably selective, electrophile-mediated process for degradation of a key transcriptional regulatory complex in primary human T cells. Considering that HDAC inhibitors have been previously shown to block T cell activation (Takahashi et al, 1996), and HDACs can also support NF-kB function (Jung et al, 2009;Kumar et al, 2017;Wagner et al, 2015), it is possible that the BPK-25-mediated loss of the NuRD complex is relevant to the T cell-suppressive activity of this compound.…”
Section: The Acrylamide Bpk-25 Promotes Degradation Of the Nurd Complexmentioning
confidence: 99%